"Identified", "probable", "possible" or "exclude": The influence of task-irrelevant information on forensic odontology identification opinion. Issue 4 (July 2022) - Chiam, Sher-Lin; Louise, Jennie; Higgins, Denice
Highlights: Participants read task irrelevant case information before comparing dental radiographs. They then gave an identification opinion using categories in INTERPOL odontology scale. Mixed effects modelling was used to analyse the outcomes. Task irrelevant context information was found to affect Identification category decision. Odds of choosing definitive categories increased with strong context supportive suggestions. Abstract: In a mass disaster situation, identification of the deceased utilising comparison of dental features is frequently heavily relied upon to facilitate rapid and accurate outcomes. The method consists of the comparison of clinical and radiographic records depicting oral structures and dentition to allow an opinion to be produced on a presumed identity. Current forensic odontology identification opinions are expressed as categories of levels of identification. Categories such as "Identified", "Probable", "Possible" and "Exclude" are used in various forensic odontology identification scales. The boundaries between the levels of the scales are not fixed; hence, category selection is highly subjective. It is uncertain how extrinsic factors such as exposure to contextual task-irrelevant information or operator experience influence category selection. In this study, forensic odontologist and dentist participants read task-irrelevant context case information containing either strong or weak identification or non-identification suggestions before evaluating and comparing pairs of true matching and non-matching dental radiographs. They were then asked to form an opinion regarding identification using one of four categories from the INTERPOL scale. Context information was found to influence categorical decisions. The magnitude and direction of influence depended on the type of participant, the true match status of the radiographs, and the strength and direction of bias of the context. The results of this study demonstrate the contextual effect and fluidity of the boundaries between the categories on the identification scale and highlight the need for stringent protocols to be developed regarding the use of these categorical scales to enable decision making to be more objective.